2016
DOI: 10.2196/publichealth.4885
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Sociodemographic Factors and HIV Risk Behaviors Associated With Social Networking Among Adolescents in Soweto, South Africa: A Cross-Sectional Survey

Abstract: BackgroundInternet access via mobile phones and computers facilitates interaction and potential health communication among individuals through social networking. Many South African adolescents own mobile phones and can access social networks via apps.ObjectiveWe investigated sociodemographic factors and HIV risk behaviors of adolescent social networking users in Soweto, South Africa.MethodsWe conducted an interviewer-administered, cross-sectional survey of adolescents aged 14-19 years. Independent covariates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…(female, aged 31-39) "We always get phones that allow Facebook and WhatsApp." (female, aged [19][20][21][22][23][24][25][26][27][28][29][30] The quantitative data showed that 27 (93.1%) participants bought airtime for voice calls using common South African prepaid services and all participants received data bundles with prepaid packages. Participants reported data to be expensive with unreliable internet connection.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…(female, aged 31-39) "We always get phones that allow Facebook and WhatsApp." (female, aged [19][20][21][22][23][24][25][26][27][28][29][30] The quantitative data showed that 27 (93.1%) participants bought airtime for voice calls using common South African prepaid services and all participants received data bundles with prepaid packages. Participants reported data to be expensive with unreliable internet connection.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…"Maybe a survey like that through WhatsApp 'cause WhatsApp is like our easiest way to communicate." (female, aged [19][20][21][22][23][24][25][26][27][28][29][30] One participant (male, aged 19-30) suggested that both an application and SMS or WhatsApp formats should be available depending on whether a participant has a smartphone or basic phone.…”
Section: Design and Formatmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, evidence indicates links between screen-based social networking and risky behaviours in adolescents. [33] Data from ISCOLE indicates that 9 -11-year-old children are spending an average of 3.3 hours on screens per day, with only 34% of children meeting the screentime guideline of <2 hours per day. [16,17] Based on the available evidence of screen time not decreasing, and the potential risks of excess screen time in adolescents, the grade remains an F. Early childhood sedentary behaviour INC Children attending preschools in low-and high-income urban areas spend approximately 73% of the preschool day sedentary, [23] which is similar to children in rural areas (70%).…”
Section: Sedentary Behaviours Fmentioning
confidence: 99%